O Primo Basílio e a relação espaço e tempo no audiovisual - Correia, Carlos Alberto [UNESP] (2015)
This study aimed at understanding the space and time settings in the audiovisual narratives of O primo Basílio, who choose to mark the loyalty registration with the original work written by Eça de Queiroz. The main question refers to: in what extent is the reconfiguration of space and time of the original work in other media? The adaptations are concentrated in the audiovisual field, being the first produced for miniseries in Brazilian TV in 1988, and the second in film format completed and released in 2007. Both have Daniel Filho as diretor, the theoretical reference and the methodology adopted in this research allowed to point out the strategies launched between different media (film, television, literature) as regards the relationship between space and time in the fictional works of O primo Basílio. The conceptual foundations that guided this research are based from notes coming from literary, communication and cinema theories, represented by Benedito Nunes (1988; 1992), Paul Ricouer (1994), Roberto DaMatta (1997), Michel de Certeau (1998), Mikhail Bakthin (1997), Vanoye e Goliot-Leté (1994), Julie Sanders (2006), Linda Hutcheon (2013) and Robert Stam (2008). As a cut, we'll analyze the internal and external environments of the bourgeois house, the street, the space occupied by the theater in the narrative, the pre and post credits and opening of the audiovisual productions, as well as chronotopic role of the media: newspapers, magazines and television. This reading was done in an attempt to understand the space and time relations in the film and in the tv show as symbolic and many meanings which enabled them to both adaptations dialogue with the novel of Eça and its historical-social-cultural issues of the late portuguese nineteenth century, set for TV production (miniseries), and its reinterpretation in Brazil, São Paulo, in 1958, present in the film...